Safety and Efficacy of Covid-19 Vaccination in Patients Undergoing Biological Treatments for Psoriasis - Potestio L; Martora F; Fabbrocini G; Battista T; Megna M (Dove Medical Press, 2023)
Luca Potestio,* Fabrizio Martora,* Gabriella Fabbrocini, Teresa Battista, Matteo Megna Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy*These authors contributed equally to this workCorrespondence: Fabrizio Martora, Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy, Tel +39 081 7462457, Fax +39 081 7462442, Email fabriziomartora92@libero.itAbstract: The introduction of biologic drugs revolutionized the treatment of psoriasis, shifting treatment goals to higher treatment outcomes and less frequent safety issues. The outbreak of Coronavirus disease 2019 (COVID-19) represented a worldwide challenge, strongly affecting lifestyle, global economy, and overall health. Among the strategies adopted to contain the spreading of the infection, vaccination is the main one. In this context, the introduction of COVID-19 vaccines raised several doubts about their effectiveness and safety in patients undergoing therapy with biological for psoriasis. Even if molecular and cellular mechanisms by which COVID-19 vaccines lead to psoriasis development have not yet been fully elucidated, vaccination itself can trigger the release of interleukin (IL)-6, interferon (IFN) and tumor necrosis factor (TNF) α by T-helper (Th)1/Th17 cells. All these cytokines are involved in psoriasis pathogenesis. Thus, the aim of this manuscript is to review current literature on the safety and effectiveness of COVID-19 vaccination in psoriasis patients undergoing treatment with biologics, in order to clarify any concerns.Keywords: psoriasis, COVID-19 vaccinations, biologic therapies, efficacy, safety